ANALYSIS OF DIFFERENCES IN PERCEPTIONS OF PROFESSIONAL ETHICS BETWEEN MALE AND FEMALE LEGAL PRACTITIONERS - Andri Nurwandri; Nur’aini; Nurul Febriyanti; Siti Khodijah MY (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the differences in perceptions of professional ethics between male and female legal practitioners in Indonesia. In the legal profession, professional ethics have a very important role to maintain integrity and public trust. However, factors such as gender are thought to influence the way legal practitioners perceive and apply these ethical principles. The research method used is Qualitative by using a literature-based approach. The data collected is analyzed using a quantitative approach to see if there is a significant difference between the perception of professional ethics between men and women. The results showed that there are differences in perspectives on several ethical issues, where women tend to emphasize the values of social justice and diversity, while men focus more on compliance with formal regulations. This research is expected to provide deeper insights into gender dynamics in the legal world and its contribution to the development of a more inclusive and equitable legal professional ethics.